INTERGENERATIONAL JUSTICE AS INTERGENERATIONAL INCLUSION: new challenges for welfare systems - Balduzzi, Giacomo; Favretto, Anna Rosa (Revista de Estudos Institucionais, 2020)
The principle of intergenerational justice is much more common in the environmental sector, but it is becoming less unusual to consider it in a social and political context. The last economic crisis has significantly increased inequality among and across generations. In several EU countries, the number of NEETs raised dramatically after the recession. Moving from the Italian case, the paper focuses on the policies recently implemented to tackle the problem. Evidence shows that solutions exclusively focused on the labour market are not sufficient to activate a full social inclusion. Hence, the authors suggest considering intergenerational justice as intergenerational inclusion and in terms of active participation and empowerment in people’s local communities. The analysis takes into account theoretical issues and practical implications of such a viewpoint, referring in particular to welfare systems and their effectiveness in facing this kind of challenge.